On System of Nonlinear Sequential Hybrid Fractional Differential Equations. (9th May 2022) - Awadalla, Muath; Abuasbeh, Kinda
Abstract : In this study, the existence and uniqueness of the solution for a system consisting of sequential fractional differential equations that contain Caputo–Hadamard (CH) derivative are verified. To study the existence and uniqueness of these solutions, some of the most important results from the fixed point theorems in Banach space were used. A practical example is also given to support the theoretical side that was obtained.